2013
DOI: 10.1088/0029-5515/53/8/083008
|View full text |Cite
|
Sign up to set email alerts
|

Electron fishbone simulations in tokamak equilibria using XHMGC

Abstract: This paper discusses the first nonlinear numerical simulation results of fishbone excitation by a magnetically trapped supra-thermal electron population with pressure profile peaked on axis due to, e.g. electron cyclotron resonance heating. The precession resonance underlying the linear instability is clearly identified. Meanwhile, mode saturation is shown to occur because of the secular resonant particle motion, pumping particles out of the radial region where the wave-particle power exchange is initially loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 44 publications
4
60
0
1
Order By: Relevance
“…There, it is shown that an n = 15 TAE in ITER, found to be the most unstable mode from previous linear stability analyses of the considered reference scenario [cf. also Vlad et al, 2006)], nonlinearly evolves up to a peak fluctuation amplitude, consistent with ω B ∼ γ L , and then decays to a steady state saturation level, which scales as ν 2/3 d , consistent with Eq. (4.137), and is typically dominated by pitch angle scattering (Chen and Parker, 2011).…”
Section: Numerical Simulations Of Perturbative Excitation Of Alfvén Esupporting
confidence: 74%
See 3 more Smart Citations
“…There, it is shown that an n = 15 TAE in ITER, found to be the most unstable mode from previous linear stability analyses of the considered reference scenario [cf. also Vlad et al, 2006)], nonlinearly evolves up to a peak fluctuation amplitude, consistent with ω B ∼ γ L , and then decays to a steady state saturation level, which scales as ν 2/3 d , consistent with Eq. (4.137), and is typically dominated by pitch angle scattering (Chen and Parker, 2011).…”
Section: Numerical Simulations Of Perturbative Excitation Of Alfvén Esupporting
confidence: 74%
“…In the following, we show that important qualitative and quantitative changes take place in the wave-particle nonlinear dynamics when the effect of "phase locked" particles in non-perturbative. When fluctuations maintain wave-particle resonance condition via "phase locking" through the nonlinear evolution, the chirping rate is proportional to mode amplitude, as observed experimentally, e.g., by (Heidbrink, 2008;Podestà et al, 2011), and in numerical simulations of nonlinear EPM evolutions Vlad et al, 2004Vlad et al, , 1999Zonca et al, 2002) as well as nonlinear fishbone dynamics Vlad et al, 2012Vlad et al, , 2013. This behavior is also demonstrated analytically for nonlinear EPM dynamics .…”
Section: Nonlinear Dynamics Of Alfvénic Fluctuations In Nonuniform Tomentioning
confidence: 63%
See 2 more Smart Citations
“…Many different works have studied this problem, retaining more effects than we shall use. The more general effects can include: gyrokinetic ions 14 , vertical plasma elongation 15 , or a different kind of energetic particles, such as barely trapped/circulating electrons 16,17 .…”
Section: Introductionmentioning
confidence: 99%